2020
DOI: 10.1021/acs.biochem.0c00019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Binding Sites on Human Serum Albumin for Somapacitan, a Long-Acting Growth Hormone Derivative

Abstract: Somapacitan, a human growth hormone derivative that binds reversibly to albumin, was investigated for human serum albumin (HSA) and HSA domain binding. Isothermal titration calorimetry (ITC) binding profiles showed high-affinity binding (∼100–1000 nM) of one somapacitan molecule and low-affinity binding (∼1000–10000 nM) of one to two somapacitan molecules to HSA. The high-affinity site was identified in HSA domain III using size exclusion chromatography (SEC) and ITC. SEC studies showed that the neonatal Fc re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…The half-life was found to be 159–195 h. This validates lipidation with fatty di-acids as a mean to prolong half-life of peptide hormones, though albumin binding of cagrilintide was not directly measured. There is rich evidence that long-acting peptides and proteins conjugated to negatively charged fatty acid derivatives exhibit strong and reversible albumin binding. ,, In addition, we have studied similar in vitro receptor assays as reported here but in the presence of varying amounts of albumin, and the data (not shown here) support that cagrilintide is a reversible albumin binder like the GLP-1 analogue semaglutide.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The half-life was found to be 159–195 h. This validates lipidation with fatty di-acids as a mean to prolong half-life of peptide hormones, though albumin binding of cagrilintide was not directly measured. There is rich evidence that long-acting peptides and proteins conjugated to negatively charged fatty acid derivatives exhibit strong and reversible albumin binding. ,, In addition, we have studied similar in vitro receptor assays as reported here but in the presence of varying amounts of albumin, and the data (not shown here) support that cagrilintide is a reversible albumin binder like the GLP-1 analogue semaglutide.…”
Section: Resultssupporting
confidence: 68%
“…There is rich evidence that long-acting peptides and proteins conjugated to negatively charged fatty acid derivatives exhibit strong and reversible albumin binding. 8,41,42 In addition, we have studied similar in vitro receptor assays as reported here but in the presence of varying amounts of albumin, and the data (not shown here) support that cagrilintide is a reversible albumin binder like the GLP-1 analogue semaglutide.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…Somapacitan is a reversible albumin-binding GH derivative in which a 1.2-kDa side chain with noncovalent albumin-binding properties is conjugated via alkylation to GH with a single amino acid substitution resulting in a 23-kDa molecule ( 22 ). Addition of a fatty acid linker to facilitate somapacitan binding to albumin and prolonging its half-life ( 23 ) has been successfully used to prolong half-life in other commercially available products within the endocrinology field ( 24-26 ). In animal models, somapacitan has been shown to directly stimulate longitudinal growth via activation of GH receptors on the peripheral tibia growth plate ( 23 ).…”
mentioning
confidence: 99%
“…Addition of a fatty acid linker to facilitate somapacitan binding to albumin and prolonging its half-life ( 23 ) has been successfully used to prolong half-life in other commercially available products within the endocrinology field ( 24-26 ). In animal models, somapacitan has been shown to directly stimulate longitudinal growth via activation of GH receptors on the peripheral tibia growth plate ( 23 ). In previous phase 3 clinical trials, somapacitan was shown to have similar efficacy to daily GH for the treatment of adult GHD, and a safety and tolerability profile in line with established evidence for daily GH ( 27-29 ).…”
mentioning
confidence: 99%
“…Furthermore, the β-chains were His6-tagged at the C-termini for simple purification. The α- and β-chains were co-expressed (1:1) in HEK293-EBNA1-6E cells (RRID:CVCL_HF20) and purified as previously reported …”
Section: Experimental Sectionmentioning
confidence: 99%